Pandemi Corona Sebagai Dalil Force Majeure Dalam Pembatalan Suatu Kontrak - Viderina Khotaro; Vania Zelin Lawrence Simanjorang; Ronald Hasudungan Sianturi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This article aims to analyze the corona pandemic categorized in Force Majeure in a contract. This problem is focused on the existence of the Corona pandemic, which can make debtors delay in fulfilling achievements or canceling contracts. How to claim Force Majeuree in a business contract. In order to approach this problem, a normative juridical legal research type is used with a descriptive-analytic nature of research aimed at describing it systematically, factually. Data - data collected through secondary data and analyzed qualitatively. Covid-19 can be categorized as force majeure, used as an excuse for the debtor not to fulfill the contract. Force majeure conditions cannot be used as a reason for canceling a contract, but renegotiation can be carried out to cancel or change the contents of a previously agreed contract. With Covid-19 being able to make debtors delay in fulfilling their achievements or canceling contracts, Covid-19 is considered to be a force majeure depending on the meaning of force majeure if it is included in the contract. As long as the affected party is able to prove that the force majeure conditions have been met. How to claim force majeure in a business contract in the Covid-19 era, claim force majeure based on appropriate legal references. The claiming parties must analyze whether a pandemic, disaster or government action applies certain provisions including the scope of force majeure accommodated in the contract.